OncoSolidDB : An Oncology-Focused Curated Database of Ligand–Target Interactions for Precision Medicine Across Major Solid Cancers. - Khamessi, Oussema; Mahjoub, Rihab; Mahjoub, Ghada; Ghedira, Kais (Cancers, 2026)
Simple Summary: Cancer treatments increasingly rely on drugs designed to bind specific molecular targets in tumors. However, information about these therapeutic ligands is scattered across multiple databases, making it difficult for researchers to access structured and oncology-focused data in a single place. To address this challenge, we developed OncoSolidDB, a curated and openly accessible database dedicated to ligands targeting solid tumors. The database integrates chemical structures, standardized identifiers, pharmacological annotations, approval history and downloadable protein structural files. Covering 243 ligands across 15 major solid cancer types, OncoSolidDB enables researchers to explore molecular properties, perform computational modeling and support drug repurposing studies. By organizing oncology-specific ligand data into a harmonized platform, this resource aims to facilitate rational drug design, accelerate translational research and improve data accessibility for the scientific community. Background/Objectives: The rapid expansion of targeted therapies has reshaped oncology by exploiting ligand-receptor interactions (LRI) to improve treatment specificity and patient outcomes. However, the data describing these ligands remain fragmented across multiple sources, limiting accessibility for researchers and clinicians. To address this gap, we developed the OncoSolidDB, the first curated and oncology-focused bioinformatics database dedicated to ligands associated with solid malignancies. Methods: OncoSolidDB integrates and harmonizes data from reliable repositories, including ChEMBL, DrugBank and the Anti-Cancer Fund, consolidating curated structural, chemical, pharmacological, and clinical annotations along with standardized identifiers. Results: The database currently encompasses 243 ligands across 15 major solid tumor types including breast, lung, colorectal, melanoma, prostate, gastric, ovarian, cervical, bladder, esophageal, head and neck, thyroid, pancreatic, renal and liver cancer (Hepatocellular Carcinoma, HCC). Each entry is annotated by standardized identifiers (DrugBank, ChEMBL), approval year, chemical structures (SMILES strings, 2D images), and downloadable protein structure files (PDB format). Temporal coverage spans 1953–2025, enabling exploration of historical trends in oncology drug approvals. The database content is suitable for bioinformatics analysis, molecular docking, virtual screening, ligand-based modeling, and drug repurposing studies. Outputs are available through a freely accessible web interface that supports search browsing by cancer type. Conclusions: By consolidating oncology-specific ligand data into a single, structured platform, OncoSolidDB offers a valuable resource for advancing drug discovery, repurposing strategies, and the rational design of next-generation targeted therapies for solid tumors. OncoSolidDB is accessible via our Bioinformatics Research PortalEinstein.